The red well : a western trio - Brand, Max, 1892-1944 (Fiver Star, 2011)
Bad News for Bad Men is just that for the Burwell clan when Jimmy Jones arrives in town to take over the Jasper Journal. Jones s uncle has given him the small-town newspaper because Jimmy's life so far has been divided into two equal halves: In the first twelve years you were a small child and a schoolboy. In the last twelve years you have tried to raise hell continually. Now, instead of being called a gunfighter, Jimmy can be called an editor. His uncle warns Jimmy that there is no news in Jasper except bad news, so Jimmy should be right at home. Notwithstanding, the rival newspaper prints only good news. Jimmy changes that from the start by stating that an act of heroism was actually a murder and that the Jasper Journal will tell readers how it happened and who committed it.